Prevalence of Antibiotic Resistance Bacteria in Aquaculture Sources in Johor, Malaysia: Prevalence of Antibiotic Resistance - Kam Kar Yern; Nor Azimah Mohd Zain; Mohd Farazi Jaafar; Mohd Helmi Sani; Mohd Suardi Suhaimi (Journal of Tropical Life Science, 2022)
The intensive use of antibiotics in aquaculture results in the proliferation of antibiotic. In this study, antibiotic resistant bacteria from six different aquaculture sources (pond of Fisheries Research Institute (FRI), and rivers of Kukup, Pulai, Pendas Laut, Sungai Melayu and Kong Kong) were isolated. These isolates were tested for antibiotic resistance against seven antibiotics via the disc diffusion method. Finally, phenotypic and genotypic identification via 16S rRNA sequencing and phylogenetic analysis were carried out. The results show that 58 out of 118 bacterial isolates are resistant to multiple antibiotics. The highest isolate resistance was observed towards rifampicin (89.66%), followed by ampicillin (79.31%) and sulfafurazole (67.24%). The isolates with multiple antibiotic resistant (MAR) index values with more than 20% were subjected to 16S rRNA gene sequencing. The majority of the bacterial strains exhibit multiple antibiotic resistance, indicating that they were isolated from highly contaminated sources based on the tested water qualities profiles, which showed the high level of turbidity and total dissolved solid (TDS) in most sampling sites with the high number of MAR bacteria obtained.Keywords: Antibiotic resistance, Multiple antibiotic resistance, Aquaculture sources,MAR index value, 16S rRNA gene sequencing